Empowering Women in the Thematic KKN Program on Waste Management into Compost Fertilizer in Selokaton Village - Khairani, Maurisa Yuant; Islam, Muqim Fakhrul; Tsani, Mutiara Latifa; Masitoh, Maharani Dewi; Rahmawati, Nanda Eka; Suwarno, Nadia Patricya Meilya; Azzahra, Laila Zurli; Akmal, Muhammad Nashif; Pratama, Mukhlis Ardi; Chusniatun, C (Universitas Muhammadiyah Surakarta, 2022)
The Student Community Service (KKN) is a routine program of the Tri Dharma of Higher Education in Indonesia, emphasizing curricular academic activities and directly involving the community. This program aims to provide skills in the form of training on the utilization of household organic waste into compost as an alternative solution in reducing the accumulation of waste at the Pancuran TPA, Selokaton Village. The Thematic KKN program for processing compost using Berkeley Method by empowering women is carried out in two sessions: a socialization session and a practical session on processing compost from organic waste. This activity was carried out by empowering women members of the PKK RT/RW 001/008 Ngaglik Sub-Village, Selokaton, Gondangrejo, Karanganyar. The result ran smoothly, and the interest and enthusiasm of the residents were high. The results of the compost are scheduled to be ready for harvest in March 2023 (60 days after manufacture).